Cultural Values and Negative Politeness in English and Russian - Larina, Tatiana (Respectus Philologicus, 2005)
The phenomenon of politeness is universal and, at the same time, is culture-specific. Traditionally, it is defined as respect and consideration for other people. However, this definition does not work in the intercultural aspect as the concepts of politeness, respect, and consideration are understood differently, and even these words have different meanings. In this paper, politeness is viewed as strategic behaviour, a system of culturallyspecific and highly ritualised communicative strategies that maximise harmonious interaction and minimise the possibility of conflict. The present research is mainly based on Brown and Levinson’s politeness theory (1978, 1987), which gives an effective mechanism for understanding interlocutors’ communicative behaviour. Still, the main emphasis is on the principal strategic differences between English and Russian negative politeness and the attempt to explain them through social organisation and cultural values. The paper gives empirical data on such Speech Acts as Command and Invitation. The comparative analysis was conducted based on ethnographic observation, questionnaires and interviews.